Studies of PMMA-(MgCF3SO3)2 gel polymer electrolytes for magnesium battery applications / Nurul Husna binti Zainol - Zainol, Nurul Husna (2013)
In the present work, the gel polymer electrolytes (GPEs) comprising of poly(methyl methacrylate) (PMMA) as a host polymer in a mixture of ethylene carbonate (EC) and propylene carbonate (PC) as a plasticizing solvent with various concentrations of magnesium triflate as a dopant salt have been prepared by the solution casting technique. The ionic conductivity of the GPE films was determined using AC impedance spectroscopy. The film containing 20 wt.% of magnesium triflate salt exhibited the highest room temperature ionic conductivity of 1.27 × 10-3 S cm-1. The conductivity-temperature studies of the GPE films follow the Arrhenius behavior with activation energy determined to be in the range of 0.18 - 0.26 eV. The transport number of magnesium ions in the GPEs was evaluated using the combination of AC impedance spectroscopy and DC polarization techniques. Fourier Transform Infrared Spectroscopy (FTIR) studies confirmed the increased in conductivity is due to increase of free ions and decrease in ion aggregates. The increase and decrease in the number of free ions can also be implied from the dielectric constant, r-frequency plots. Thermal studies indicate that the GPE films are stable over a wide temperature range, 30 C – 130 C. XRD and FESEM studies revealed that the increased in amorphous region of GPE films lead to higher conductivity of the films. The electrochemical stability of the GPE film has been tested using linear sweep voltammetry (LSV). Studies based on AC impedance and cyclic voltammetry (CV) confirm Mg2+ ion conduction in the GPE film. The highest conducting GPE film was used as an electrolyte in MgGPEMnO2 cell. The GPE film appears to be excellent substitute for the liquid electrolyte in rechargeable magnesium batteries.